Strategy of the School’s Principal in Improving Teacher’s Performance for Curriculum Independence - Deby Melina; Nur Ahyani; Rohana Rohana (Wahana Didaktika : Jurnal Ilmu Kependidikan, 2023)
The goal of this study was to identify and evaluate the supporting and impeding elements in the implementation of the principal’s strategy to enhance teacher teaching performance utilizing the autonomous curriculum at SMK Aisyiyah Palembang. This study uses descriptive qualitative research to obtain trustworthy information regarding the procedures used in data collection using observation, interviews, and documentation. The administrators and instructors at SMK Aisyiyah Palembang served as the study’s informants. According to the study’s findings, the principal has tried to enhance teachers’ abilities to teach utilizing the autonomous curriculum, specifically through education and training. implementation of a private curriculum for teachers and school administrators. Mentoring programs and independent curriculum training were also implemented in addition to the aforementioned technique. In this study, there were additional challenges like the creation of ATP, Teaching Modules, and the somewhat complex methods or media that needed to be used, as well as a lack of infrastructure to support them in the form of learning media, student handbooks, teacher handbooks, and assessments on the independent curriculum. beginning with formative and summative evaluations.